Recent advances of enzymatic reactions in ionic liquids: Part II - Elgharbawy, Amal A.M.; Moniruzzaman, Muhammad; Goto, Masahiro (Elsevier, 2020)
As a biocompatible and designer solvents, ionic liquids (ILs) are extensively used for enzymatic conversion of substrates, particularly those that are insoluble or sparingly soluble in water and common organic solvents. More than a decade ago, the first-generation ILs involved in enzymatic reactions generally comprised an imidazolium cation and non-coordinating anions, such as tetrafluoroborate and hexafluorophosphate. Recently, focus has shifted to more environmentally acceptable second- and third-generation ILs comprising enzyme compatible cations (e.g., cholinium salts) and anions, such as amines and amino acids. A wide range of such ILs have been derived from readily available renewable resources and used in biocatalytic reactions. Compared with first-generation ILs, the use of enzymes in second- and third-generation ILs provides better activity and stability, and they are also attractive from both an environmental and an economic viewpoint. In this review, we report the recent advances of enzymatic reactions in second- and third-generation ILs. The intention of this review is not to cover first-generation ILs, but rather to update and overview the potential approaches developed within the last ten years for enzymatic reactions in second- and third-generation ILs.